Correction: A colour opponent model that explains tsetse fly attraction to visual baits and can be used to investigate more efficacious bait materials. - Roger D Santer (Public Library of Science (PLoS), 2015)
[This corrects the article DOI: 10.1371/journal.pntd.0003360.].